Why only humans have language - Dunbar, R (Oxford University Press, 2010)
This chapter has three main objectives. First, it briefly summarizes the reasons why language might have evolved, and what we are to make of these. It then considers what this has to tell us about why only the hominin lineage evolved the capacity for language. Finally, it revisits the author's previous analyses (Aiello and Dunbar 1993) on the timing of language evolution in the hominin fossil record using new estimates for all the equations involved, in order to explore the sequence by which language might have evolved, and the transitional states involved.